2018
DOI: 10.1002/humu.23541
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations in theSETnuclear proto-oncogene, encoding a component of the inhibitor of histone acetyltransferases (INHAT) complex in patients with nonsyndromic intellectual disability

Abstract: The role of disturbed chromatin remodeling in the pathogenesis of intellectual disability (ID) is well established and illustrated by de novo mutations found in a plethora of genes encoding for proteins of the epigenetic regulatory machinery. We describe mutations in the "SET nuclear proto-oncogene" (SET), encoding a component of the "inhibitor of histone acetyltransferases" (INHAT) complex, involved in transcriptional silencing. Using whole exome sequencing, four patients were identified with de novo mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…This inhibition is most likely accomplished by masking histone lysines from being acetylated, and the consequence is to silence HAT-dependent transcription. Mutations in the gene encoding SET are linked to developmental delay and intellectual disabilities as well as to autosomal dominant 58 (MRD58), a form of mental retardation, characterized by significantly below average general intellectual functioning associated with delayed development, impairments in adaptive behavior, language delay and speech impairment [94][95][96]. Interestingly, SET interacts with intracellular domains of the gonadotropin-releasing hormone (GnRH) receptor and differentially regulates receptor signaling to cAMP and calcium in gonadotrope cells [97].…”
Section: Discussionmentioning
confidence: 99%
“…This inhibition is most likely accomplished by masking histone lysines from being acetylated, and the consequence is to silence HAT-dependent transcription. Mutations in the gene encoding SET are linked to developmental delay and intellectual disabilities as well as to autosomal dominant 58 (MRD58), a form of mental retardation, characterized by significantly below average general intellectual functioning associated with delayed development, impairments in adaptive behavior, language delay and speech impairment [94][95][96]. Interestingly, SET interacts with intracellular domains of the gonadotropin-releasing hormone (GnRH) receptor and differentially regulates receptor signaling to cAMP and calcium in gonadotrope cells [97].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the regulation of diverse genes through charged interaction between the acidic domain of SET and the lysine/arginine-rich domain of the interacting proteins, demonstrated here for transcription factors p53 and FOXO1, suggest aberrant expression of SET would set off a ripple effect on a wide range of gene expressions due to altered transcription and changes of chromatin conformations under physiological conditions. Moreover, a recent report has shown that truncation mutations in set in human are associated with nonsyndromic intellectual disability, even though four out of five of those mutations in set present as a heterozygote in the patients, suggesting reduced expression of SET can also cause disruption of SET dependent regulation and defects in brain development and functions 23 . Therefore, better understanding of the defects in relation to SET regulated proteins could potentially lead to the development of novel therapeutic remedies such as targeting acetylation/deacetylation to circumvent the dysregulation by SET in cancer and mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Though many studies have illustrated the role of TTSN proteins in diverse cellular functions, our knowledge about their contribution to human pathology is very limited. Exome sequencing has recently detected autosomal dominant variants in SET, the gene for the SET nuclear protooncogene, as cause for non-syndromic intellectual disability in five unrelated patients (6).…”
mentioning
confidence: 99%